2013
DOI: 10.1111/jph.12115
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Phylogenetic Analysis of Potyviruses, Carlaviruses and Allexiviruses in Garlic in Sudan

Abstract: Allium sativum L. samples of three cultivars grown in Sudan were shown to contain several of the common garlic viruses of the genera Potyvirus, Carlavirus and Allexivirus. In particular, Onion yellow dwarf virus (OYDV), Leek yellow stripe virus (LYSV), Garlic common latent virus (GarCLV), Garlic virus A (GVA), Garlic virus B (GVB), Garlic virus C (GVC) and Garlic virus X (GVX) were detected by reverse transcription polymerase chain reaction (RT-PCR) assay using degenerate genus-specific and virus-specific prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The genetic diversity of allexivirus populations has been reported when comparing the CP and the replicase sequences, indicating population differentiation (Chen et al, 2001;Melo-Filho et al, 2004;Mohammed et al, 2013). Our data indicates that phylogenetic clustering among allexivirus isolates was independent of geographical area (Figure 1B).…”
Section: Phylogenetic Analyses and Taxonomic Impactsupporting
confidence: 66%
“…The genetic diversity of allexivirus populations has been reported when comparing the CP and the replicase sequences, indicating population differentiation (Chen et al, 2001;Melo-Filho et al, 2004;Mohammed et al, 2013). Our data indicates that phylogenetic clustering among allexivirus isolates was independent of geographical area (Figure 1B).…”
Section: Phylogenetic Analyses and Taxonomic Impactsupporting
confidence: 66%
“…Overall, phylogenetic studies showed that Ethiopian garlic virus isolates are in most cases clustered together and their geographical origin and phylogenetic relatedness are often not correlated. Several studies conducted in other countries indicated similar evolutionary phenomena and attributed it to the fact that international exchange of vegetative planting materials between countries contributing to high diversity and rapid evolution of garlic viruses (Bereda et al 2017;Koo et al 2002;Mohammed et al 2013;Taglienti et al 2018;Wylie et al 2012). Historically, Ethiopia has been actively involved in trade and germplasm exchange of horticultural spices including Allium crops with Asian, Middle East, European and North African countries.…”
Section: Discussionmentioning
confidence: 90%
“…Serological detection such as DAS-ELISA has limitations in the production of specific antibodies against virus species from mixed infection (Pramesh et al, 2012). Nucleotidebased detection or molecular techniques such as Reverse Transcription -Polymerase Chain Reaction (RT-PCR) proved more highly specific, reliable and sensitive than ELISA for viral diagnostics (Mohammed et al, 2013;Jones et al, 2017).…”
Section: Introductionmentioning
confidence: 99%